An Operational View on Foaming and Slopping Control in Top-blown BOS Vessels - Brämming, Mats (Luleå tekniska universitet, Mineralteknik och metallurgi, 2015)
Slag formation plays a decisive role in all steelmaking processes. In top-blowing Basic Oxygen Steelmaking (BOS) i.e., in the LD process, an emulsion consisting of liquid slag, dispersed metal droplets, undissolved particles and solid precipitates will, together with process gases, form an expanding foam. Extensive research has defined the parameters that govern the foaming characteristics of BOS slag-metal emulsions. It is a well-known fact that certain process conditions in the Basic Oxygen Furnace (BOF) will lead to excessive foam growth, forcing foam out through the vessel opening (mouth). This process event is commonly known as slopping. Slopping results in loss of valuable metal, equipment damage, lost production time, unsafe work environment and pollution. A literature survey covering the slopping phenomena has been carried out, as well as a deeper investigation into the causes behind slopping on the BOF type LD/LBE at SSAB Europe, Luleå, equipped with an automatic system for slopping registration using image analysis Good slag formation and foam-growth control in order to avoid slopping is primarily accomplished by taking preventive “static” measures. The most common pre-blowing operational conditions favouring foam growth and, hence, slopping were found to be linked to oxygen lance positioning, hot metal Si and Mn contents, scrap quality and large additions of iron oxide bearing materials. Improved slopping control may be achieved by developing oxygen lance control schemes with automatic adjustment of the distance between the lance tip and the metal bath (i.e., the lance gap) according to scrap quality and ore additions. If “static” measures cannot be effectuated, a set of in-blow slopping preventive measures is needed. For such “dynamic” measures to be effective, it is necessary to have a system for slopping prediction. Trials with vessel vibration measurements for indirect foam height estimation in industrial scale BOFs, type LD/LBE, have been carried out. FFT spectrum analysis was applied in order to ...